Fault Detection of an Engine Using a Neural Network Trained by the Smooth Variable Structure Filter - Ahmed RM; Sayed MAE; Gadsden SA; Habibi SR (Institute of Electrical and Electronics Engineers (IEEE), 2011)
A multilayered neural network is a multi-input, multi-output (MIMO) nonlinear system in which training can be regarded as a nonlinear parameter estimation problem by estimating the network weights. In this paper, the relatively new smooth variable structure filter (SVSF) is used for the training of a nonlinear multilayered feed forward network. The SVSF is a recursive sliding mode parameter and state estimator that has a predictor-corrector form. Using a switching gain, a corrective term is calculated to force the network weights to converge to within a neighbourhood of the optimal weight values. SVSF-based trained neural networks are used to classify engine faults on the basis of vibration data. Two faults are induced in a four-stroke, eight-cylinder engine. Furthermore, a comparative study between the popular back propagation method, the extended Kalman filter (EKF), and the SVSF is presented. Experimental results indicate that the SVSF is comparable with the EKF, and both methods outperform back propagation. © 2011 IEEE.
Keywords: 46 Information and Computing Sciences; 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; 4611 Machine Learning